Analisis Risiko Kesehatan Lingkungan terhadap Paparan Debu pada Pekerja Pasir Batu di Desa Lonjoboko Kabupaten Gowa - Tenriawi, Westy; Leonard, Franita (Jurnal Penelitian Multidisiplin Ilmu, 2025)
Lonjoboko Village has mining potential including sand, river stone, soil, mountain stone and sirtu. The presence of a mining industry in the midst of community life has provided employment opportunities and business opportunities, but must still pay attention to health risks, especially for dust exposure. This study was conducted to predict risks and manage health risks due to dust exposure in sand collectors in Lanjoboko Village, Parangloe District, Gowa Regency. This type of research is descriptive research with a cross-sectional design and the approach used is the Environmental Health Risk Analysis method. The results of the environmental health risk analysis indicate that there are 2 points at risk due to PM10 exposure in sand collectors in Lonjoboko Village. These two points include Depot 1 (1 ilir) and Depot 2 (1 ilir) whose RQ values are 5.4 and 2.7 respectively, which means RQ> 1. While TSP exposure is still within safe limits with all RQ values ? 1, so risk management is needed to control PM10 concentrations in the air.